2008
DOI: 10.1038/sj.bjp.0707581
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sphingosine 1‐phosphate receptors involved in constriction of isolated cerebral arteries with receptor null mice and pharmacological tools

Abstract: Background and purpose: Sphingosine 1-phosphate (S1P) selectively and potently constricts isolated cerebral arteries, but this response has not been pharmacologically characterized. Experimental approach: The receptor subtype(s) involved in S1P-induced cerebrovascular constriction were characterized using genetic (S1P 2 and S1P 3 receptor null mice) and pharmacological tools (phospho-FTY720, a S1P 1/3/4/5 receptor agonist; SEW2871, a S1P 1 receptor agonist, JTE-013, a S1P 2 receptor antagonist, VPC23019, a S1P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
5
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(143 citation statements)
references
References 36 publications
4
133
5
1
Order By: Relevance
“…Coupled with various G-proteins, these S1P receptors mediate diverse biological actions. S1P induces contraction of rabbit gastric smooth muscle through S1P 1 and S1P 2 (Zhou and Murthy, 2004), contraction of cat esophageal smooth muscle cells through S1P 2 , contraction of cerebral arteries of mice through the S1P 3 (Salomone et al, 2008), and contraction of airway smooth muscles through the S1P 2 (Rosenfeldt et al, 2003). In the present study, treatment of ICC with S1P resulted in depolarization of the membrane and increased induction of tonic inward pacemaker currents, suggesting that S1P may mediate excitatory action on intestinal motility.…”
Section: Discussionsupporting
confidence: 58%
“…Coupled with various G-proteins, these S1P receptors mediate diverse biological actions. S1P induces contraction of rabbit gastric smooth muscle through S1P 1 and S1P 2 (Zhou and Murthy, 2004), contraction of cat esophageal smooth muscle cells through S1P 2 , contraction of cerebral arteries of mice through the S1P 3 (Salomone et al, 2008), and contraction of airway smooth muscles through the S1P 2 (Rosenfeldt et al, 2003). In the present study, treatment of ICC with S1P resulted in depolarization of the membrane and increased induction of tonic inward pacemaker currents, suggesting that S1P may mediate excitatory action on intestinal motility.…”
Section: Discussionsupporting
confidence: 58%
“…For example, S1P-induced vasoconstriction was observed in canine basilar arteries, 71 in rodent cerebral arteries, 59,60 and in mesenteric resistance arteries from aged rats. 76 In general, higher concentrations of S1P are required to elicit vasoconstriction (several 100 nanomolar to micromolar) than required for S1P-induced vasorelaxation, which typically shows an EC 50 in the low nanomolar range.…”
Section: Vasoconstriction Pathways Elicited By Sphingosine-1-phosphatmentioning
confidence: 99%
“…In support of this hypothesis, pharmacological as well as genetic experiments have shown that S1P 2 and/or S1P 3 receptor subtypes coupled with ROK may mediate S1P-provoked vasoconstriction in VSMCs. 60,70,77,78 It has also been shown that pharmacological inhibition of NOS activity leads to an enhancement of S1P-elicited vasoconstriction, 76,79 and conversely, S1P fails to induce vasorelaxation in eNOS null animals. 29 Further support for differential receptor-mediated vasorelaxation and vasoconstriction responses comes from studies in which S1P 1 antagonists were found to potentiate S1P-induced vasoconstriction responses in rodent cerebral arteries; however, effects of S1P 1 receptor antagonism are lost when the endothelium is removed from the blood vessel preparation.…”
Section: Vasoconstriction Pathways Elicited By Sphingosine-1-phosphatmentioning
confidence: 99%
See 1 more Smart Citation
“…Les récepteurs de S1P concourent aussi à la régulation du tonus vasculaire, régulant à la fois la contraction et la relaxation des cellules musculaires lisses. Le S1P 3 [12] et le S1P 2 [13] seraient responsables de l'effet vasoconstricteur de la S1P. Le S1P 3 induit la relaxation des cellules musculaires lisses via la production de NO à partir de l'endothélium [14].…”
Section: Rôles Physiopathologiques De La S1punclassified